Potential propagation seedling of Ramie (Boehmeria nivea) from various types of stem cuttings - Rahman Side, Taufiq Hidayat; Yamin, Mayasari; Mulyani, Sri; Aji, Agung Pangestu; Ayunawati, Luthfi (Kultivasi, 2024)
Ramie is a fiber-producing plant that can replace cotton as a raw material for the textile industry. In general, ramie plants are reproduced using rhizomes, but it takes a long time, around two years, to be used as a source of planting material. Therefore, other sources of explants besides rhizomes are required, such as stem cuttings. Explants from stem cuttings are quickly available and only need 2-3 months to be used as planting material. This study aims to determine the potential of effective stem cuttings that can be used as planting material for the propagation of ramie seedlings. The research was conducted from July to December 2021 at the experimental garden in the Indonesian Instruments Standardization Testing Center for Sweetener and Fiber Crops, Malang, East Java. The research used a Completely Randomized Design (CRD) consisting of four treatments of ramie seedling material of the Ramindo 1 variety, namely rhizome, shoot cuttings, middle stem cuttings, and basal stem cuttings. Each treatment was repeated 5 times. The result showed that all parameters had a significant effect. Ramie seedling source from basal stem cuttings showed the best growth percentage (92%), stem diameter (4.8 mm), and plant wet weight (44.6 g). Shoot cuttings showed the best number of roots (31.6), plant height (60.8 cm), and number of leaves (41.4). Cuttings from shoot and basal stems can be used as planting material for producing ramie seeds other than rhizomes.